2009
DOI: 10.2989/ajms.2009.31.2.12.884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fishing on a temperate reef community in South Africa 1: ichthyofauna

Abstract: Exploitation of temperate reef fish not only affects the target species but potentially changes the composition of reef fish assemblages. This study investigated the effect of fishing on the ichthyofaunal community at protected and exploited sites around the Goukamma Marine Protected Area (MPA) on the South African temperate south coast. Abundance and size frequency data from 273 standardised angling and 44 underwater visual census sites were analysed with generalised linear modelling and multivariate techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…The higher abundance of roman at protected sites may account for the lower crinoidea abundance there as they are the main food source for roman (Buxton 1984, AG unpublished data). Götz et al (2009) also found higher abundances of strepie Sarpa salpa, blacktail Diplodus hottentotus and steentjie Spondyliosoma emarginatum at protected sites. It is likely that the lower algae abundance found at those sites is a result of the higher abundances of these species, which are partially herbivorous (i.e.…”
Section: Effects Of Fishing On the Subtidal-reef Communitymentioning
confidence: 73%
See 3 more Smart Citations
“…The higher abundance of roman at protected sites may account for the lower crinoidea abundance there as they are the main food source for roman (Buxton 1984, AG unpublished data). Götz et al (2009) also found higher abundances of strepie Sarpa salpa, blacktail Diplodus hottentotus and steentjie Spondyliosoma emarginatum at protected sites. It is likely that the lower algae abundance found at those sites is a result of the higher abundances of these species, which are partially herbivorous (i.e.…”
Section: Effects Of Fishing On the Subtidal-reef Communitymentioning
confidence: 73%
“…Here, we attempted to overcome these limitations by interpreting the results from a larger study by considering the key components of the reef ecosystem, i.e. invertebrates and algae and fish (Götz et al 2009). At Goukamma, fishing was identified as the single-most important factor determining fish abundance (Götz et al 2009).…”
Section: Effects Of Fishing On the Subtidal-reef Communitymentioning
confidence: 99%
See 2 more Smart Citations
“…Dyer 1995, Punt and and environmental effects (van der Lingen et al 2006a, Watermeyer et al 2008. Near Tsitsikamma, fishing on a temperate reef community was found to affect the size and abundance of roman Chrysoblephus laticeps (Götz et al 2009a), the dominant fish species in catches, allowing their competitors to increase and also affecting benthic communities (Götz et al 2009b). Small marine protected areas have been found to benefit resident fish populations like roman that are heavily exploited (Kerwath et al 2008), whereas seasonal or spatial closures can be used for wide-ranging or migratory species (Grantham et al 2008).…”
mentioning
confidence: 99%